KONSTRUKSI STORYTELLING PADA OBJEK WISATA DI KAWASAN SOLO RAYA - Anjang Priliantini; Andre N. Rahmanto; Monika Sri Yuliarti; Albert Muhammad Isrun Naini; Christina Tri Hendriyani; Mahfud Anshori (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2023)
The impact of the Coronavirus has devastated many sectors of life, including tourism as the sector most affected. To restore the country’s economy, the tourism sector is slowly starting to be allowed to operate with strict supervision over the implementation of health protocols and CHSE (Clean, Health, Safety, Environment Sustainability). However, this does not necessarily restore the level of tourist visits. Therefore, efforts and tourism promotion strategies are needed to showcase the attractiveness of tourist destinations while ensuring the safety and security of tourists at tourist sites. One of the tourism promotion strategies is storytelling. Storytelling is an application of art in preparing narratives or stories about a tourist attraction. This paper aims to review the application of narrative preparation techniques for tourist attractions in Solo Raya which is carried out by tour guides. The activities carried out are training for tour guides who are members of the Himpunan Pramuwisata Indonesia Cabang Solo Raya. As a result, the tour guide has been able to compose storytelling by involving all elements, namely setting, character, conflict, plot, and theme. However, the tour guide cannot optimize the story's appeal due to too much to be conveyed in one object.  ---  Hantaman virus Corona telah meluluhlantahkan banyak sektor kehidupan, termasuk pariwisata sebagai sektor yang paling terdampak. Untuk memulihkan perekonomian negara, sektor pariwisata perlahan mulai diizinkan beroperasi dengan pengawasan ketat atas penerap-an protokol kesehatan dan CHSE (Clean, Health, Safety, Environment Sustainability). Namun hal tersebut tidak serta-merta mengembalikan tingkat kunjungan wisata. Karenanya, dibutuhkan upaya dan strategi promosi wisata untuk menampilkan daya tarik destinasi wisata sembari menjamin keamanan dan keselamatan wisatawan di lokasi wisata. Salah satu strategi promosi pariwisata adalah storytelling. Storytelling adalah sebuah penerapan seni dalam penyusunan narasi atau cerita tentang suatu objek wisata. Tulisan ini merupakan makalah yang bertujuan untuk mengulas penerapan teknik penyusunan narasi atas objek wisata di Solo Raya yang dilakukan oleh pramuwisata. Kegiatan yang dilakukan berupa pelatihan bagi pramuwisata yang tergabung pada Himpunan Pramuwisata Indonesia Cabang Solo Raya. Hasilnya, pramuwisata telah mampu menyusun storytelling dengan melibatkan seluruh elemen, yaitu setting, tokoh, konflik, alur, dan tema. Namun demikian, pramuwisata dinilai belum dapat mengoptimalkan daya tarik cerita akibat terlalu banyak yang ingin disampaikan dalam satu objek.